iCITES 2018 Focuses on Technology, Engineering and Science - Nur Laila, Afandi (2018)
Pekan, 2 March – International Conference of Innovative Technology, Engineering and Science 2018 (iCITES 2018) has been held recently and has succeeded in gathering nearly 100 local researchers in various areas of engineering and science and technology such as green and material frontiers, innovative robotics and automation, renewable and green energy, sustainable manufacturing as well as data analytics and internet-of-things (IoT).